Mathematical modelling of the stages of solid tumours growth and the nonlocal interactions in cancer invasion - Onana Eloundou, Jeanne Marie (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.